2015
DOI: 10.4103/0973-1482.140836
|View full text |Cite
|
Sign up to set email alerts
|

Responding to family requests for nondisclosure: The impact of oncologists′ cultural background

Abstract: All oncologists felt that the family request for nondisclosure was difficult, with many cultural and emotional nuances to take into consideration. Some immigrant Australian oncologists who had a similar cultural background as the patient/family, felt they could better understand the desire for nondisclosure. Irrespective of their cultural background, all oncologists acknowledged that breaking bad news had to be done in a gentle, gradual manner. The study suggests a need to develop a culturally sensitive cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 24 publications
0
29
1
3
Order By: Relevance
“…This is the norm in western cultures (Seifart et al., ) and is reflected around the world through an increasing trend towards full patient disclosure (Chaturvedi et al., ; Ichikura et al., ). Our findings are in contrast with recent reports from Canada (Oliffe, Thorne, Hislop & Armstrong, ) and Australia (Chittem & Butow, ) that suggest that cancer patients from non‐Western cultures may prefer less information and do not desire full disclosure. Like Gautam and Nijhawan () two decades ago, we found that majority of Indian patients want to be told the truth.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is the norm in western cultures (Seifart et al., ) and is reflected around the world through an increasing trend towards full patient disclosure (Chaturvedi et al., ; Ichikura et al., ). Our findings are in contrast with recent reports from Canada (Oliffe, Thorne, Hislop & Armstrong, ) and Australia (Chittem & Butow, ) that suggest that cancer patients from non‐Western cultures may prefer less information and do not desire full disclosure. Like Gautam and Nijhawan () two decades ago, we found that majority of Indian patients want to be told the truth.…”
Section: Discussioncontrasting
confidence: 99%
“…Australia (Chittem & Butow, 2015) that suggest that cancer patients from non-Western cultures may prefer less information and do not desire full disclosure. Like Gautam and Nijhawan (1987) two decades ago, we found that majority of Indian patients want to be told the truth.…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted by Savio and George (Naveen & Anice, 2013) mentioned that nurses have difficulty talking to someone who has a distinct cultural and linguistic background. Another study conducted by Chittem and Butow (2015) stated that the language differences could lead to misunderstanding in interpreting the information provided. Therefore, in the nursefamily relationship mutual respect is needed to be able to minimize misunderstanding due to differences in cultural culture and language.…”
Section: Discussionmentioning
confidence: 99%
“…47,4954 These and other cultural differences are commonly cited as barriers to appropriate end-of-life care. 55 Additional literature suggests how Western HCPs should respond to noncollusion requests.…”
Section: Alternative Perspectivesmentioning
confidence: 99%